A comparative study of the social play behavior of four - and five-year old preschoolers from two schools. - Hilado, Teresa Lucia D.
This is a descriptive study comparing the social play behavior of four - and five-year old preschoolers enrolled in two different schools (an academically-oriented, traditional private school and a structured-environment model). The researcher identified the philosophy, programs and practices of these two schools and observed 52 children (24 from School A and 28 from School B) using M.B. Parten's developmental stages of social play. A two-way analysis of variance was performed on the trasnformed data to determine whether there are school and/or age inferred that certain key elements within the school philosophy, programs, and practices contribute to the development of certain social play activities. Significant school differences were observed fort two categories namely: solitary play and cooperative play. School B children were observed to engage in solitary independent play more frequently compared to School A children. These children were also less cooperative compared to their counterparts. Significant age differences were observed for the parallel play category. No interaction effect between age and school on any of the categories was found.